Models and methods for assessing multi-factor authentication security mechanisms - Горбенко, Юрий Иванович; Олешко, Инна Викторовна (Eastern-European Journal of Enterprise Technologies, 2013)
The results of the research are given in the paper, the main purpose of which is the development of the emulator of industrial objects, which is characterized by portability, versatility on a reproduction of transfer functions of typical control objects, support of standard configurations of input/output signals, support of the possibility of remote control and readjustment. Using the modern hardware provided by the scientific and production association «Owen» for research conducting and the software platform CoDeSys, a portable and flexible in the readjustment industrial object emulator was developed based on the controller PLC100-RL. The functional diagram of connection of such an emulator to the mounted automated control system is given. The structures of programs for the reproduction of basic transfer functions of typical industrial objects are proposed. The process of setting the configuration of input and output channels of the emulator was considered in details. Flexibility of readjustment is provided by the possibility of reprogramming, and universality – by the presence of discrete and analog inputs/outputs, with standard signal levels 0- 20mA, 0- 1V. The Ethernet interface allows remote control and readjustment. For complex and distributed objects it is possible to complicate the emulator by the cascade inclusion of individual controllers-emulators. The proposed methods and approaches extend the range of the use of network technologies and programmable logic controllers, namely they can be used for improvement of performance and expansion of the functionality of existing emulators of industrial objects, simplification and cost reduction of the stage of adjusting the systems of automated control of industrial processes